The Role Of The Class Iib Tanjung Pura Detention Center In Carrying Out Rehabilitation Of Women As Prisoners - Anugrah Kesatria Kaban; T. Riza Zarzani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The importance of rehabilitation for addicts or victims of drug abuse is to heal the physical, mental and mental conditions for addicts and victims of drug abuse. It isvery likely that addicts experience health problems as a result of drug abuse, so that the existence of rehabilitation services or health services will be able to improve the quality of life of addicts or drug abusers. The purpose of this study was to find out the legal regulations regardingrehabilitation, implementation of rehabilitation for narcotics convicts in class IIB Tanjung Pura and the role of class II Bprison in tanjung Pura in rehabilitating fostered residents. This research is included in the descriptive research with the type of empirical juridical research using qualitative analysis methods. From the results of the study it is known that the legal basis and regulations related to the rehabilitation of convicts who abuse narcotics are Law Number 35 of 2009 concerning Narcotics, Law Number 12 of 1995 concerning Corrections, Regulation of the Minister of Health of the Republic of Indonesia Number 46 of 2012 concerning Procedures for Implementing Medical Rehabilitation For Addicts, Abusers, and Victims of Narcotics Abuse. SEMA Number 4 of 2010, Concerning Placement of Abusers, Victims of Abuse, Narcotics Addicts Into Medical and Social Rehabilitation Institutions and SEMA Number 3 of 2011 concerning Placement of Victims of Narcotics Abuse in Institutions of Medical and Social Rehabilitation. Rehabilitation in Class IIB Tanjung Pura Detention Centre is carried out in the form of medical rehabilitation, non-medical rehabilitation and social rehabilitation with stages in the form of providing initial information and screening and assessment and In carrying out the rehabilitation of inmates by the Tanjung Pura detention Centre Class IIB it has an impact There is a change in behavior and mentality, The emergence of awareness to stop consuming drugs, the emergence of obedience in worship and the percentage of awareness of drug addicts has increased